The logistics of autonomous shipping and the AEGIS project - Psaraftis, Harilaos N.; Zis, Thalis; Reche-Vilanova, Martina (My University, 2023)
The European Union (EU) transport policy recognizes the importance of the waterborne transport systems as key elements for sustainable growth in Europe. By 2030, 30 % of total road freight over 300 km should shift to rail or waterborne transport, and more than 50 % by 2050. Thus far, this ambition has failed. Horizon 2020 project AEGIS (for Advanced, Efficient and Green Intermodal Systems) proposes a new waterborne transport system for Europe that is green, robust, flexible, more automated and autonomous, and able to connect both rural and urban terminals. The purpose of this paper is to describe work and preliminary results from this project. To that effect, and in order to assess any solutions contemplated in AEGIS, a comprehensive set of Key Performance Indicators (KPIs) have been defined, and three specific use cases within in Europe are defined and evaluated according to these KPIs. KPIs represent the criteria under which the set of solutions developed under AEGIS are evaluated, and also compared to non-AEGIS solutions. They are grouped under economic, environmental and social KPIs. KPIs have been selected after a consultation process involving AEGIS partners and external Advisory Group members.
Keywords: Autonomous Shipping; Autonomous Terminals; Green Logistics; Key Performance Indicators; Maritime Logistics; Shipping Decarbonisation